The Analysis of Optimism Values in Hazel’s Grace the Fault in Our Stars Movie: Analisis Nilai Optimisme dalam Film Hazel's Grace the Fault in Our Stars - Indratha, Faras Bagas Indratha; Candraningrum, Dewi (Universitas PGRI Madiun, 2024)
The significance of optimistic thinking is crucial for enhancing the quality of life for individuals. This research aims to explore the value of optimism in the character Hazel Grace from The Fault in Our Stars. The study employs Snyder's theory of optimism, as discussed in Goleman's work (2002), as its foundational framework. Utilizing qualitative research methods, data were collected through various techniques, including data reduction, selection, presentation in the form of quotations, and drawing conclusions as the final step. Upon analyzing Hazel Grace's optimism, the findings revealed that she exhibits five indicators of high expectations, four traits of resilience (not easy to give up), five instances of self-motivation, two indicators of high self-confidence, and four traits reflecting her determination not to surrender. This research is limited to examining the optimistic values of Hazel Grace as the central character. Future studies could expand this analysis to assess the optimism levels of all characters within the narrative